UTILIZATION OF AROMATIC SULPHONES IN THE UPPER SHOES LEATHER TANNING PROCESS - Sofwan Siddiq Abdullah; Kuntoro; Fadzkurisma Robbika; Thoyib Rohman Hakim (Politek ATK Yogyakarta Press, 2023)
Technology of leather tannery is influenced by laws and developments in technology, both domestically and internationally. Current research has a major focus on discovering new process technologies and materials that make the leather processing technology more optimal and environmentally friendly. Currently, most of the leather tanning processes in Indonesia still have normative stages, which consist of beam house operation, tanning, post-tanning (neutralization, retanning, dyeing, fatliquoring) and finishing stages. The purpose of this study is to alter the post-tanning procedure for upper shoes by using aromatic sulfones. By using aromatic sulfones, leather can be tanned without the requirement for neutralization. The results of this study are expected to educate tanneries and give them another choice for performing tanning techniques that are more efficient, more reasonably priced, and meet standards for the quality of finished leather. With the addition of aromatic sulfones, wet blue goat skin post-tanning can be finished in 225 minutes (3 hours 45 minutes), or roughly 21.43% of the typical processing time. This process modification can both speed up the tanning process and consume less water because no fresh water is needed during the post-tanning phase. Water savings in the post-tanning process can reach 400% of the total water used. With these advantages, it is believed that the tanning process for leather would become more effective and affordable. Furthermore, by using less water during the post-tanning process, liquid waste can also be decreased. In terms of organoleptics and mechanics, the rubbing resistance of post-tanning leather with with the addition of aromatic sulfones meets the requirements/standards for upper shoes.